The diaspora Nigerians’ image problem of drug and fraud: A case study of the Malaysian-Indonesian experience through newspaper reports - Owoyemi, Musa Yusuf; Din, Abdul Kadir; Ahmad Sabri, Ahmad Zaharuddin Sani (Science Publication, 2015)
It is no longer news that the economic and social problems in Nigeria have led to mass migration of Nigerians to other parts of the world for better job opportunities and/or education.South-East Asia has had its fair intake of some of these Nigerians especially in recent times.However, some unscrupulous Nigerians in their bid to make quick money have used the opportunity afforded by some of their host nations to commit crimes ranging from drug trafficking to internet fraud.The negative activities of these few have had a bad impact on the image of the entire citizenry of Nigeria in diaspora and this has led to stereotyping and prejudices-at times with dire consequences.Using the textual analysis method, this paper looks at the activities of some of these criminal minded Nigerians in diaspora through newspaper reports in Malaysia and Indonesia with a view to pinpointing the problems they are creating in these societies, their negative effect on other Nigerians and what solution(s) could possibly be implemented in curbing their activities.